Mobile Adhoc Networks and Networking – Integrating Risk Profiles into Intrusion Prevention Systems to Improve Predictive Intrusion Prevention (Global Journal of Computer Science and Technology, 2023)
Intrusion Prevention in computer networking refers to the set of techniques and technologies used to detect and prevent unauthorized access malicious activities and attacks on a network It involves actively monitoring network traffic identifying potential threats or anomalies and taking action to mitigate or block those threats In the realms of Mobile Adhoc Networks and computer networking substantial work has pointed to the gaps experienced with respect to proactively identifying and mitigating risks and network malicious behaviours and attacks This paper seeks to highlight the existing intrusion detection and prevention techniques currently being utilized in MANETS and general computer networking and how the introduction of the novel Risk Profile approach based on Axiom theory can be utilized or integrated to improve the accuracy of existing models of Intrusion Detection and Prevention systems With a dual purposed aim of bolstering public confidence in utilizing MANETs and improving the security posture of networks which depend heavily on Security controls to protect their information and assets
Keywords: IDS; IPS; manets; attacks; anomalous; risk; Malicious